The post-graduate public health school of Siena (Italy): ten years of experience (Italian Journal of Public Health, 2011)
Introduction: Public universities and private schools in all countries have substantially expanded the postgraduate courses as a sign that degree is often not sufficient to ensure access to employment.Aim: To present the experience of an Italian Post-Graduate Public Health School (SPGPHS) from 1996-2005.Activity: We made a review of the Italian legislation governing the postgraduate training and we studied the structure of Post Graduate School in Public Health in several Italian and foreign prestigious universities.Results: The SPGPHS was attended by about 1,000 students from all the Italian Regions. 100 scientific papers were published and/or presented at national/international conferences; SPGPHS has also proven to be able to completely finance itself.Conclusions: Postgraduate university courses are becoming very important and attenders range widely in age. Many students undertake Postgraduate courses to improve their work position, to attain Continuing Medical Education credits, but at the same time, to gather multidisciplinary scientific knowledge and to acquire professional skills. SPGPHS has proven to be able in financing itself responding to the market logic which is guided by performance and efficiency aspects.
Keywords: teaching; university; public health; post-graduate degree; Italy